Caracterização de um biossurfactante produzido por Pseudomonas cepacia cct6659 e sua aplicação em solo impactado por derivados de petróleo - Silva, Elias José da (2015)
Biosurfactants are amphipathic compounds capable of displaying a variety of surface-active properties that, among other functions, assist microorganisms that degrade and solubilize hydrophobic substrates. In recent years, the biosurfactants have been investigated as possible replacements for synthetic surfactants, especially because they have large environmental applications. In this sense, the bacterium Pseudomonas cepacia CCT6659 cultured with 2% soybean waste frying oil and 2% corn steep liquor as substrates produced a biosurfactant with potential to be applied in bioremediation of soils. Firstly, the biosurfactant was produced, isolated and submitted to Thin Layer Chromatography, being classified as an anionic biomolecule with lipid and carbohydrate combination of 75 and 25% respectively. The characterization by proton nuclear magnetic resonance (1H and 13C NMR) revealed the presence of carbonyl, olefinic and aliphatic groups, being observed typical spectra of lipids. Four sets of biodegradation experiments were carried out with a soil contaminated by hydrophobic organic compounds amended with sugar cane molasses in the presence of indigenous consortium as follows: set 1 soil + bacterial cells, set 2 soil + biosurfactant, set 3 soil + bacterial cells + biosurfactant, set 4 soil without bacterial cells and biosurfactant (control). Interestingly, when biosurfactant and bacterial cells were used (set 3), significant oil biodegradation activity occurred (83%) in the first ten days of experiments, while maximum degradation of the organic compounds (above 95%) was observed in sets 1 , 2 and 3 between 35 and 60 days. It is evident from the results that the biosurfactant alone or its producer specie is capable of promoting biodegradation to a large extent.